2007
DOI: 10.1253/circj.71.855
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Transradial Stenting for Unprotected Left Main Coronary Artery Stenoses

Abstract: s opposed to 1-or 2-vessel coronary artery diseases (CAD), patients with unprotected left main artery disease carry poor outcomes if left unrevascularized. 1,2 Percutaneous coronary intervention (PCI) is regarded as a potential alternative management of unprotected left main coronary artery (ULMCA) disease to coronary artery bypass graft surgery (CABG) in selected patients due to comparable short-term clinical results. [3][4][5] Given the high percentage of distal bifurcation lesions and the large vessel diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…[6][7][8][9][10][11][12] The transradial arterial approach (TRA), which is a fairly simple route of access 13,14 for catheter-based coronary intervention, has been developed for more than 15 years and since the safety and efficacy of this method was fully discussed and validated, 13,15 it has become a widely used approach, especially in Asia, for elective percutaneous coronary intervention (PCI). [15][16][17][18][19] Recent studies has further indicated that TRA is safe and efficacious for elective coronary angiographic studies of outpatients, 20 elective left main coronary intervention, 21 cerebral angiographic studies or vertebral or carotid stenting. 22,23 So currently, the TFA and TRA are the most popular vascular access routes for various types of PCI worldwide, but while the safety and efficacy of the TFA approach for acute myocardial infarction (AMI) patients undergoing primary PCI have been extensively discussed, 3,24,25 relevant issues for using the TRA for primary PCI have not been fully investigated 26 in an era when TRA for primary PCI is already daily practice in some medical centers.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] The transradial arterial approach (TRA), which is a fairly simple route of access 13,14 for catheter-based coronary intervention, has been developed for more than 15 years and since the safety and efficacy of this method was fully discussed and validated, 13,15 it has become a widely used approach, especially in Asia, for elective percutaneous coronary intervention (PCI). [15][16][17][18][19] Recent studies has further indicated that TRA is safe and efficacious for elective coronary angiographic studies of outpatients, 20 elective left main coronary intervention, 21 cerebral angiographic studies or vertebral or carotid stenting. 22,23 So currently, the TFA and TRA are the most popular vascular access routes for various types of PCI worldwide, but while the safety and efficacy of the TFA approach for acute myocardial infarction (AMI) patients undergoing primary PCI have been extensively discussed, 3,24,25 relevant issues for using the TRA for primary PCI have not been fully investigated 26 in an era when TRA for primary PCI is already daily practice in some medical centers.…”
mentioning
confidence: 99%
“…We previously reported the feasibility and safety of transradial stenting for ULMCA stenosis. 4 The 1-year TLR rate of left main coronary lesions and cardiac death rate were 14.2% and 3.5%, respectively. Park and Kim reported acceptable long-term outcomes of PCI with DES to treat ULMCA stenoses.…”
Section: Article P 705mentioning
confidence: 95%
“…9 Finally it is time to consider TRI as the primary approach for emergency PCI for ST elevation myocardial infarction (STEMI). Bleeding complications are a frequent problem in PCI for STEMI because of the use of IIbIIIa inhibitor or tPA.…”
Section: Article P 2050mentioning
confidence: 99%